Enhancement Effects of Biosurfactant Produced by Pseudomonas aeruginosa MTCC 2297 and Pseudomonas fluorescens on Sugar Cane Bagasse Composting - P. K. Sivakumaar, Parthasarathi, R.* and (Journal of Ecobiotechnology, 2010)
Biosurfactant produced by Pseudomonas aeruginosa MTCC2297 and Pseudomonas fluorescens (a Mangrove forest isolate) was added to the Sugar cane bagasse decomposing process to initiate and enhance the production of reducing sugars. Both isolates produced a glycolipid biosurfactant, namely a rhamnolipid that was confirmed by biochemical and analytical studies. The surface tension of fermentation broth reduced from 73 to 34.2 mN/m by P. aeruginosa MTCC 2297 and from 76 to 29 mN/m by P. fluorescens. Sugar cane bagasse decomposing process was attempted by two different methods, adding pure rhamnolipid and on-site production of it were compared. The study revealed that rhamnolipid concentration of 0.75gl-1 was optimum for composting process and the optimum temperature for compost pile production was 32°Cfor the first 48h subsequently 35°C for the next 48h. At the optimum temperature for this two-stage fermentation, the production of reducing sugar could be increased to 15.73 gl-1 for P. aeruginosa MTCC 2297 and for the P. fluorescens reducing sugar increased to 15.88 gl-1, both experiments resulted in higher values than that of the treatment without rhamnolipid sample. The results indicate that application biosurfactant could possibly reduce the composting period. As the compost pile production of rhamnolipid does not require the purification process, the production cost reduced significantly. ——————————————————————————————————– Department of Microbiology, Faculty of Agriculture, Annamalai University, Annamalai Nagar, Chidambaram, Tamil Nadu, India-608002. *Corresponding author, Email: parthasangi@yahoo.com, Mob: +91-9842059688 Cite This Article As: Parthasarathi, R. and P. K. Sivakumaar. 2010. Enhancement Effects of Biosurfactant Produced by Pseudomonas aeruginosa MTCC 2297 and Pseudomonas fluorescens on Sugar Cane Bagasse Composting. J. Ecobiotechnol. 2(3): 33-39.